FACTOR ANAYSIS THE CAUSE OF DELAYED INTERVENTION WITH LENGTH OF STAY PATIENTS ADMISSION IN EMERGENCY DEPARTMENT OF PROF. DR. W.Z. JOHANNES GENERAL HOSPITAL KUPANG - Maria Fatimah Fouk; Titin Andri Wihastuti; Dewi Kartikawati Ningsih (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2017)
Overcrowding patients is a crisisÂ problem in hospital and plays a significant role as a front line in hospital which performing good and bad quality of care. Length of Stay (LOS) patients admission measurement indicator toward service process and patients density marker. Length of stay has important essence in reviewing process because helping to identify the cause of action delay and elongated LOS. EDLOS is influenced by input and trough put factor. Input factor: age, coming time, main complaint and co-morbidity. Trough put factor: triage level, door to doctor, the quickness in laboratory check, the quickness in specialist consultation and patients transfer to nursing room, staffing. This study is aimed to analyze the correlation of causing factor on action delay with LOS patients admissionÂ in Prof. Dr. W. Z. Johannes Public Hospital Kupang. This study uses cross sectional approach and quota sampling by the number of 200 patients and nurses also doctors. Data was collected by observation sheet. Result of this study shows that there are significant correlation between co-morbidity with LOS patients admission (p value = 0,001 and r = - 0,227), between the quickness of specialist consultation with LOS patients admission (p value = 0,001 and r = 0,238) and between patients transfer to nursing room LOS patients admission (p value = 0,000 and r = 0,699). Based on the result of linear regression test, it is concluded that factor that has very close correlation with LOS patients admission patients transfer to nursing room (p value < 0,001, regression coefficient 0,015 and correlation coefficient 0,774). Conclusion: co-morbidity, specialist consultation and patients transfer to nursing room is LOS patients admission predictor. Developing centralized bed control dan transporter is mandatory for decrease overcrowding and LOS patients admission in emergency department.